2018
DOI: 10.35608/ruraled.v33i3.408
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Perceptions of Rural STEM Teaching: Implications for Rural Teacher Retention

Abstract: Rural school districts often struggle with attracting and retaining high-quality teachers, especially in science subject areas. However, little is known about STEM in-service teachers’ lived experiences of rural teaching as they relate to retention. In this phenomenographical study, six rural in-service science teachers were interviewed regarding their perceptions of the benefits and challenges of teaching in rural schools in general, and teaching science subjects in particular. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 11 publications
4
88
0
1
Order By: Relevance
“…Teachers often return to communities where they were educated (Boyd, Lankford, Loeb, & Wyckoff, 2005). Connecting with the community (within the school, the school district, and the city where the student live) can help teachers increase their feelings of connectedness and resilience (Goodpaster, Adedokun, & Weaver, 2012; Wright et al, 2019). Tom and Scott were encouraged to follow through with their reform vision, in part, because of the community support they fostered, demonstrated by the end‐of‐the‐year banquet and donations from local charities and multiple news stories across the country about their program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers often return to communities where they were educated (Boyd, Lankford, Loeb, & Wyckoff, 2005). Connecting with the community (within the school, the school district, and the city where the student live) can help teachers increase their feelings of connectedness and resilience (Goodpaster, Adedokun, & Weaver, 2012; Wright et al, 2019). Tom and Scott were encouraged to follow through with their reform vision, in part, because of the community support they fostered, demonstrated by the end‐of‐the‐year banquet and donations from local charities and multiple news stories across the country about their program.…”
Section: Discussionmentioning
confidence: 99%
“…Mentors can work with teachers to identify the source and potential resolution to their discontentment, helping them reflect on past experiences (Emirbayer & Mische, 1998; Southerland et al, 2011). They can also help teachers identify whether they feel like they belong in school or local communities (Goodpaster et al, 2012; Skaalvik & Skaalvik, 2011). The current study demonstrated how peer mentors, as Tom and Scott were to one another, can provide a powerful support system.…”
Section: Discussionmentioning
confidence: 99%
“…Herrington and Herrington (2001) state that within the first five years of rural and regional practice, geographical isolation and lack of professional development is likely to result in many professionals leaving their country locations and even the profession. Schools in regional areas and small towns have greater difficulty filling vacancies than those in cities due to lack of available and suitably qualified people (Goodpaster, Adedokun & Weaver, 2012). This can result in schools in regional areas often being staffed with relatively new and inexperienced teachers, in turn this can have a negative impact on school efficiency (Goodpaster, et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While many schools in the United States have already integrated technology into classroom learning (Howley et al 2011), this learning opportunity is not available to the same extent in all districts or schools. In comparison to urban and suburban neighborhoods, schools in rural communities more often lack the technology access to serve large numbers of underrepresented students (Sundeen and Sundeen 2013;Blanchard et al 2016;Goodpaster et al 2009). Inadequate funding and budgetary concerns may deter technology acquisition in rural schools, leaving students without regular access to basic tools such as computers or eliminating student opportunities to experience advanced technologies such as 3D printers (Sundeen and Sundeen 2013, p. 8).…”
Section: Introductionmentioning
confidence: 99%